State of the art in anti-cancer mAbs - Chiavenna, S. M. (J Biomed Sci, 2017)
Following Milstein’s discovery, the monoclonal antibodies (mAbs) became a basic tool for biomedical science. In cancer field, since the first mAb was approved by the FDA a great improvement took place making of them a therapeutic option for many cancer types in the current clinical practice. Today, mAbs are being developed to target different molecules with different mechanisms of action and its target potential is unlimited. However, this huge and fast growing new field needs to be organized to better understand the treatment options we have to confront different cancer diseases. Current cancer targeted immunotherapies aim to achieve different goals like the regulation of osteoclast function, the delivery of cytotoxic drugs into tumor cells and the blockade of oncogenic pathways, neo-angiogenesis and immune checkpoints. Here, we reviewed the most relevant therapeutic mAbs for solid tumors available in current clinical practice.